In vitro the Antiprotozoal Activity of Zingibar ‎officinale Alcohol Extract and Metronidazole in ‎Entamoeba gingivalis which Isolated from ‎Patients with Periodontal Disease (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Entamoeba gingivalis is parasite found in mouth, causes dental disease. This parasite discovered in dental plaque, the last studies found relation between E. gingivalis and periodontal disease. In present study collected 30 samples collected from patient with age (20-30) years, result show infection with this parasite 46.6%. These samples are cultured in TYSGM-9 media, and then treated with different concentration of alcoholic extract ginger and metronidazole which show inhibited growth of parasite at (25, 50, 75,100 μg/ml. )